Предмет: Алгебра,
автор: wasiadaun
УПРОСТИТЕ ВЫРАЖЕНИЕ :
3(x-1)+(x-2)-x=
5n-3(n+2)+(n-6)=
m-(2n-6)+3(m-3)=
2(3x+1)-(x-2)-3x=
Ответы
Автор ответа:
0
1)=3х-3+х-2-х=3х-5
2)=5п-3п-6+п-6=3п-12
3)=м-2п+6+3м-9=4м-2п-3
4)=6х+2-х+2-3х=2х+4
2)=5п-3п-6+п-6=3п-12
3)=м-2п+6+3м-9=4м-2п-3
4)=6х+2-х+2-3х=2х+4
Похожие вопросы
Предмет: Математика,
автор: shakullina
Предмет: Русский язык,
автор: zhumabekdamir2009
Предмет: Математика,
автор: ivlevaksenia440
Предмет: Физика,
автор: Na7tushe4ka
Предмет: География,
автор: Кэнй